Vertebrate roadkills in three road types in the central mountainous region of Veracruz, Mexico - Cervantes-Huerta, Rodolfo; Escobar, Federico; García-Chávez, Juan Héctor; González-Romero, Alberto (Instituto de Ecología, A.C., 2018)
This study evaluates the influence of the road type and infrastructure (culverts) on the numbers of vertebrates killed on the Xalapa – Puebla highway (section: Banderilla – Amozoc) in the central mountainous zone of the state of Veracruz. The study was carried out on three different road types (varying according to the number of lanes and type of structure that separates the lanes) along which sites were selected where there was a culvert considered as a potential wildlife crossing. Roadkills at each site were counted and related to the presence – absence of culverts, the slope of the right of way with respect to the road, as well as the road type. A greater number of roadkills occurred in the two-lanes highway followed by the highway divided by central vegetation barrier and the highway with central barrier of concrete wall. In none of the types of road studied were found an effect of the presence of culverts on the number of vertebrates killed. In addition, a negative relationship was found between the number of roadkills and the slope of the right of way. This study helps to understand the factors that limit the crossing of vertebrates on the roads and discusses the implications of road infrastructure planning - construction for wildlife.